How Does the Consumers’ Attention Affect the Sale Volumes of New Energy Vehicles: Evidence From China’s Market - Jiang, Zhe; Long, Yin; Zhang, Lingling (Frontiers in Energy Research, 2021)
The promotion of new energy vehicles is a grand plan across countries to achieve carbon neutrality and air purification. The sale volume of new energy vehicles is affected by many factors, yet it is the attitude of consumers themselves that has the final decisive role. We use four representative Baidu search indexes as the variables representing the attention of consumers and take variables of economic, population, and income as control variables for regression analysis from the national and sub-economic regional perspectives respectively. Results show that search indexes of ‘new energy vehicle’, ‘new energy vehicles battery’, and ‘charging pile’ all have significant positive impacts on the sales of new energy vehicles to varying degrees while the index of ‘automobile spontaneous combustion’ has a significant negative impact on the sale volume. This study, therefore, verifies that the consumer attention represented by search indexes is an important yet uncovered factor affecting the sale volume of new energy vehicles. Besides, due to people's prejudice against spontaneous combustion accidents of new energy vehicles, consumers have a cognitive bias about the safety of new energy vehicles especially in less developed areas of China.